The nuclear environmentalist : is there a green road to nuclear energy? - Juan José Gómez Cadenas (Springer, 2015)
This book discusses renewable energy, including the thesis that nuclear energy, although by no means problem-free, can be a viable source of concentrated, reliable and carbon free electricit, as part of a diversified and rational mix of electricity sources.